Neo-developmentalism and trade unions in Brazil - Andréia Galv\~ao (University of Bath, Centre for Development Studies (CDS), 2016)
This article deals with the Brazilian labour movement during Workers' Party governments, discussing its organizational reconfiguration and its ability to influence politics. It identifies the main actions and demands put forward by the trade union movement after the arrival of the PT to the Federal Government and the achievements in terms of social and labour rights. It argues that unions' ability to formulate policies contrasts with their limited intervention in the decision making process. It holds also that despite organizational divisions, union federations have presented a common agenda and a certain unity of action. This unity, however, is affected by the heterogeneity of concepts and union practices. Union federations increased their institutional participation and the majority unionism adopted a political moderation perspective, provoking criticism and triggering splits. Political moderation does not mean the absence of struggles and contentions but in this context, the strikes and mobilizations, even increasing, were not sufficient to approval of the union agenda. If the different union strategies and forms of struggle generated tensions and conflicts, especially among the minority and the hegemonic tendencies, at the same time it dynamized the Brazilian labour movement.
Keywords: 330; Labour; Trade Unions; Politics; Development; Neo-liberalism; Latin America